2006
DOI: 10.4049/jimmunol.177.7.4718
|View full text |Cite
|
Sign up to set email alerts
|

Galectin-3 Induces Death of Candida Species Expressing Specific β-1,2-Linked Mannans

Abstract: Lectins play a critical role in host protection against infection. The galectin family of lectins recognizes saccharide ligands on a variety of microbial pathogens, including viruses, bacteria, and parasites. Galectin-3, a galectin expressed by macrophages, dendritic cells, and epithelial cells, binds bacterial and parasitic pathogens including Leishmania major, Trypanosoma cruzi, and Neisseria gonorrhoeae. However, there have been no reports of galectins having direct effects on microbial viability. We found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
163
0
4

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 205 publications
(170 citation statements)
references
References 71 publications
3
163
0
4
Order By: Relevance
“…It has been suggested that galectin-3 may serve as a pathogen pattern recognition receptor to visualize PAMPs from bacteria (19,20), parasites (21,22), and fungi (23,24). Moreover, it has been reported that galectin-3 interacts with LPS via both NЈ and CЈ terminals (25).…”
mentioning
confidence: 99%
“…It has been suggested that galectin-3 may serve as a pathogen pattern recognition receptor to visualize PAMPs from bacteria (19,20), parasites (21,22), and fungi (23,24). Moreover, it has been reported that galectin-3 interacts with LPS via both NЈ and CЈ terminals (25).…”
mentioning
confidence: 99%
“…79 In addition to the indicated roles of this lectin in promoting phagocytic uptake and prevention of microbial dissemination, galectin-3 has a direct fungicidal activity upon binding to the specific b-M present in the C. albicans cell wall. 24 In this work, we show that the increased binding of cek1 mutants is partially impaired by lactose (a blocking agent of galectins binding site) suggesting a role for this receptor in cek1 recognition. Through western blotting and immunofluorescence analysis of C. albicans interaction with murine macrophages, we uncovered an increased stimulation of galectin-3 secretion caused by cek1 infection, when compared to the wild type strain, and possible increased expression at the macrophage membrane and cytoplasm.…”
Section: Discussionmentioning
confidence: 89%
“…24 Given the increased detection of b-M in the cell surface of cek1 mutants, we analyzed whether galectin-3 could be relevant in this interaction. We first assessed the effect of lactose on C. albicans binding to murine macrophages, given its role as inhibitor of galectins carbohydrate binding site.…”
Section: Cells (mentioning
confidence: 99%
See 1 more Smart Citation
“…However, studies with knockout mice and mutant C. albicans strains have shown the importance of TLR4 [10]. Galectin-3 is a β-1,2 mannan receptor that specifically recognizes the pathogenic yeast C. albicans but not the non-pathogenic Saccharomyces cerevisiae [11] and to exerts direct fungicidal effect [12]. TLR1 and TLR6, known to form heterodimers with TLR2, have been recently shown to have no or mild effect on macrophage recognition of C. albicans [13].…”
Section: Recognition Of Fungimentioning
confidence: 99%